Evropska sredstva - Pleterski Puharič, Rok (Pravnik, 2024)
This article provides a concise overview of the legal regulations governing spatial and development planning in relation to the utilisation of European funds. It aims to explore how Slovenia can more optimally leverage the financial resources available from the European Union to foster economic growth, innovation, and sustainable development. The capacity of programmes and projects to absorb European cohesion funds is critically dependent on the timely approval or adoption of national programme documents. This is particularly important for ensuring the timely and efficient use of European cohesion funds. Strategic and implementation documents in the field of spatial and development planning are also essential at both national and regional levels. Although there have been consistent changes to legal regulations to enhance the efficient use of available European Union financial resources, there remain further opportunities for refinement.
Keywords: absorpcijska sposobnost; absorption capacity; development planning; EU funds; evropska sredstva; municipalities; občine; pokrajine; prostorsko načrtovanje; regions; spatial planning